Reflections of Student-teachers on School Internship of 2–year B.Ed. Programme - MPM, Fathima Jaseena; K., Vijayan. (JOURNAL OF INDIAN EDUCATION, 2020)
Preparing a competent teacher who possesses desired theoretical knowledge, pedagogical skill, and classroom managerial skill is the responsibility of any teacher education programme. Due to several constraints like ineffective curriculum, rigidness in its execution, lack of proper orientation to the prospective teachers, and insufficient duration of practice teaching programme made most of the teacher education institution to fail developing competent teacher. There was a general criticism that, the secondary teacher education curriculum of one year programme was not enough in terms of time to provide any scope for the student teacher to fledge with experiential learning in the school curriculum. Thus, NCTE Regulations 2014 recommended the enhancement of the duration to two year to the existing one year programme. It also highlighted that; the duration of School Internship Programme should be of minimum 20 weeks duration. Most of the Universities and Teacher Education Institutions started its implementation from 2015 onwards. It is in this context that this study has been conducted, which aims to investigate the challenges and concerns, if any, faced by prospective teachers during their extended school internship programme. The data has been collected from 300 prospective teachers from different teacher education institutions from Kozhikode and Mallpuram districts under Calicult University, Kerala. The result of the study reveals that there are many challenges and issues such as lack of time in organisation of curricular and co-curricular activities, writing of reflective journals, etc. as reflected by the student teachers. Majority of prospective teachers.